A Theory of Saving and Portfolio Selection - Douglas, A. (Review of Economic Studies, 1968)
Journal Article A Theory of Saving and Portfolio Selection Get access A. Douglas A. Douglas University of California, Berkeley Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 35, Issue 4, October 1968, Pages 453–463, https://doi.org/10.2307/2296772 Published: 01 October 1968